KAIRÓS, EL INSTANTE DECISIVO - Gilabert Tormo, Maria (THÉMATA. Revista de Filosofía, 2015)
En este artículo haremos un recorrido conceptual por el término y las problemáticas de la fotografía, utilizando la figura de Cartier-Bresson como hilo conductor. Tras intentar determinar las características que la definen, analizaremos la relación de la misma con la pintura; trataremos de ver, a continuación, diferentes opiniones y posturas acerca de si puede o no considerarse arte; y apuntaremos, en última instancia, ciertos cambios en el concepto de belleza que ha conllevado esta nueva forma de reproducir el mundo. In this article we will explore the concept and problems of photography, using the figure of Cartier-Bresson as the thread that runs through the entire essay. After trying to determine the characteristics that define it, we will analyses the relationship between photography and painting. Then, we will attempt to see the different opinions and points of view about whether photography can or cannot be considered art. Finally, we will state certain changes in the concept of beauty that has led to this new way of reproducing the world.